The recontextualisation of youth wellbeing in Australian schools. Issue 5 (17th September 2019) - Whatman, Susan; Thompson, Roberta; Main, Katherine
Abstract : Purpose: The purpose of this paper is to suggest how well-being messages are recontextualized into school-based contexts from an analysis of national policy and state curricular approaches to health education as reported in the findings of two selected case studies as well as community concerns about young people's well-being. Design/methodology/approach: A cross-sectional review of Australian federal and state-level student well-being policy documents was undertaken. Using two case examples of school-based in-curricular well-being programs, the paper explores how discourses from these well-being policy documents are recontextualized through progressive fields of translation and pedagogic decision making into local forms of curriculum. Findings: Pedagogic messages about well-being in Australia are often extra-curricular, in that they are rarely integrated into one or across existing subject areas. Such messages are increasingly focused on mental health, around phenomena such as bullying. Both case examples clearly demonstrate how understandings of well-being respond to various power relations and pressures emanating from stakeholders within and across official pedagogic fields and other contexts such as local communities. Originality/value: The paper focusses on presenting an adaptation of Bernstein's (1990) model of social reproduction of pedagogic discourse. The adapted model demonstrates how "top-down" knowledge production from the international disciplines shaping curriculum development and pedagogic approaches can be replaced by community context-driven political pressure and perceived community crises. It offers contemporary insight into youth-at-risk discourses, well-being approaches and student mental health.